2007
DOI: 10.1111/j.1365-2966.2006.11235.x
|View full text |Cite
|
Sign up to set email alerts
|

The stellar mass content of distant galaxy groups

Abstract: We have obtained near-infrared imaging of 58 galaxy groups, in the redshift range 0.1 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 43 publications
7
59
0
Order By: Relevance
“…Applying a total-to-stellar-mass ratio of 100, appropriate for clusters with a velocity dispersion in the range 425-800 km s −1 (Balogh et al 2007), in a similar way to the approach of McCarthy et al (2007) for a structure at z = 1.5, we obtain a total mass of ∼6 × 10 13 M , which is consistent with the mass obtained above for the sphere circumscribing the high-density region. Castellano et al (2007) reported three X-ray sources within the high-density region, one coinciding with the peak of their galaxy density contours and including a late-type galaxy of a peculiar morphology.…”
Section: Galaxy Overdensity and Mass Containedsupporting
confidence: 73%
See 1 more Smart Citation
“…Applying a total-to-stellar-mass ratio of 100, appropriate for clusters with a velocity dispersion in the range 425-800 km s −1 (Balogh et al 2007), in a similar way to the approach of McCarthy et al (2007) for a structure at z = 1.5, we obtain a total mass of ∼6 × 10 13 M , which is consistent with the mass obtained above for the sphere circumscribing the high-density region. Castellano et al (2007) reported three X-ray sources within the high-density region, one coinciding with the peak of their galaxy density contours and including a late-type galaxy of a peculiar morphology.…”
Section: Galaxy Overdensity and Mass Containedsupporting
confidence: 73%
“…Although this Butcher-Oemler effect has been disputed, the general conclusion still stands (e.g., Ellingson et al 2001;Tanaka et al 2005;Andreon et al 2006;Tran et al 2007;Fassbender et al 2008). Balogh et al (2007) find that, for a given stellar mass and redshift, fewer galaxies in groups show strong [O ii] emission than in field galaxies. The evolution of star formation rate appears to depend on both galaxy mass and galaxy environment (Baldry et al 2006).…”
Section: Introductionmentioning
confidence: 96%
“…It could be explained by a different time of assembly of galaxies in haloes of different masses, a nature mechanism that results in a more evolved galaxy population in groups and clusters, at fixed stellar mass, in a given redshift bin (see Gao et al 2005;Balogh et al 2007).…”
Section: Detection Of the Possible Signature Of Environmental Effectsmentioning
confidence: 99%
“…are primarily determined by the mass of the dark matter halo in which the galaxy resides (Cooray & Sheth 2002), and that, at a given mass, in overdense environments dark matter haloes assemble at higher redshifts than in underdense environments (Gao et al 2005). This framework could provide a simple way of explaining the observed trends in colors with galaxy luminosity, mass and environment, at low (De Propris et al 2004;Blanton & Berlind 2007) and also at high redshifts (Wilman et al 2005a;Balogh et al 2007), without resorting to any specific mechanisms acting in groups. Two large recent redshift surveys, VVDS and DEEP2, have addressed this problem by studying both groups (Gerke et al 2007;Cucciati et al 2009b) and local density field measurements (Cucciati et al 2006;Cooper et al 2006Cooper et al , 2007, although both studies considered both luminosity selected samples, a choice that, as we discuss later, offers only partial insight into the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable work on more common, lower-mass haloes at z > 0.3 -the progenitors of today's massive clusters -is more difficult and hence more limited, but several studies have shown that group galaxies indeed evolve differently from the field, at least for z < 0.8 (e.g. Wilman et al 2005;Balogh et al 2007;Poggianti et al 2008;Rudnick et al 2009;McGee et al 2011;Knobel et al 2013). At z > 0.8, however, little is known about galaxy evolution in group and low-mass cluster haloes.…”
mentioning
confidence: 99%